2020
DOI: 10.1097/ccm.0000000000004161
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting α5 Subunit-Containing γ-Aminobutyric Acid Type A Receptors Attenuates Cognitive Deficits After Traumatic Brain Injury

Abstract: Objectives: Cognitive deficits after traumatic brain injury are a leading cause of disability worldwide, yet no effective pharmacologic treatments exist to improve cognition. Traumatic brain injury increases proinflammatory cytokines, which trigger excess function of α5 subunit-containing γ-aminobutyric acid type A receptors. In several models of brain injury, drugs that inhibit α5 subunit-containing γ-aminobutyric acid type A receptor function improve cognitive performance. Thus, we postulated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…33,34 Ono-160 was described in a most recent patent (WO 2015/115673 A1), and L-655,708 has been widely investigated in preclinical studies. 6,23,24,35 Primary hippocampal neuronal culture…”
Section: Selection Of Five α5-namsmentioning
confidence: 99%
“…33,34 Ono-160 was described in a most recent patent (WO 2015/115673 A1), and L-655,708 has been widely investigated in preclinical studies. 6,23,24,35 Primary hippocampal neuronal culture…”
Section: Selection Of Five α5-namsmentioning
confidence: 99%
“…The trials that involved the introduction of a new task (specifically trials 1, 2, 5, and 8) were used to assess problem-solving ability. 13,23 Trial 1 was the “door open” task, during which both the door and underpass were open. In trial 2, the “underpass” task was introduced, whereby the door was closed, and only the underpass remained open.…”
Section: Methodsmentioning
confidence: 99%
“…For the behavioral studies, we selected a sample size of 20 to 24 animals per group, based on previous experience with the puzzle box assay. 13,23 A post hoc analysis revealed that this sample size provided 90% power to detect a treatment effect size of f = 0.41.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…It has been shown that hippocampus dysfunction is associated with cognitive deficits following a TBI [6,8,9]. Existing treatments for TBI primarily focus on immediate neurosurgical procedures and long-term behavioral rehabilitation, but few treatments are sufficient to improve TBIinduced cognitive deficits [10,11]. TBI differs from other diseases in that it involves different periods after the injury.…”
Section: Introductionmentioning
confidence: 99%